(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2023)
In this study, the effect of changing geometry of the heat sinks on forced convection heat transfer and laminar fluid flow features in a rectangular channel has been studied experimentally and numerically of the circular fins and circular-cut fins heat sinks with straight continuous fins as reference comparison. For the experimental conditions, the Reynolds number value varied as 2418.56- 806.19 according to the variation of flow rate values. The wall heat flux was varied as 11.11, 31.11, 58.05, 83.05, 112.5, 155 kW/m2. COMSOL Multiphysics was used to solve the governing equations under laminar flow conditions with air as the working fluid. To verify the accuracy of the analytical model, the simulation's optimal design was constructed and experimentally validated. The results indicated that circular-cut fins enhanced heat dissipation. Nusselt numbers for CCFs with Reynolds numbers of 797.7 and 2393.1 are roughly 83.6 and 132.4 at a heat flux of 11.1, kW/m2.